2015
DOI: 10.1007/s00520-015-2610-3
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of missed delirium in patients referred to palliative care in a comprehensive cancer center

Abstract: Sixty-one percent of patients with a diagnosis of delirium by a palliative care specialist were missed by the primary referring team. Patients with MD were frequently referred for pain. Universal screening of cancer patients for delirium is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
97
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 131 publications
(103 citation statements)
references
References 36 publications
3
97
0
3
Order By: Relevance
“…Rates of unrecognized delirium, defined as delirium diagnosed by an expert assessor after the diagnosis was not made by the patient’s treating physicians and nurses, ranged from 55% to 70% in 2000–2001 2, 3 and still remain around 60% in 2015. 4 Delirium is a complex and challenging condition, and a synthesis of current evidence should optimize clinical care. The goals of this review were (1) to summarize the current approaches to diagnosis and treatment of delirium, (2) to highlight recent advances, and (3) to underscore critical gaps in knowledge where future research is needed to advance the field.…”
Section: Introductionmentioning
confidence: 99%
“…Rates of unrecognized delirium, defined as delirium diagnosed by an expert assessor after the diagnosis was not made by the patient’s treating physicians and nurses, ranged from 55% to 70% in 2000–2001 2, 3 and still remain around 60% in 2015. 4 Delirium is a complex and challenging condition, and a synthesis of current evidence should optimize clinical care. The goals of this review were (1) to summarize the current approaches to diagnosis and treatment of delirium, (2) to highlight recent advances, and (3) to underscore critical gaps in knowledge where future research is needed to advance the field.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoactive delirium is the most common subtype and is more likely to be underdiagnosed compared with hyperactive or mixed delirium. 4,74 Delirium can be clinically assessed using a variety of screening instruments, with the Confusion Assessment Method 75 being the most well-validated and widely used approach. The diagnosis is established according to DSM-5 60 or ICD-10 criteria.…”
Section: Gap 4: Patients With Cancer Are Not Routinely Screened Fomentioning
confidence: 99%
“…Delirium is also a common, often under-recognized 4 neuropsychiatric problem associated with substantial morbidity, mortality, and a high potential impact on decision-making ability. The vast majority of studies on the prevalence and impact of delirium have focused on hospitalized general medicine or postoperative patients, as opposed to older adults with cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective review of 771 consecutive palliative care inpatient consults at a large cancer hospital found that 61% of delirium diagnoses were missed by the primary referring team and that hypoactive delirium was the most common subtype (63%). 16 Given this high prevalence, cancer patients should be screened with an appropriate assessment on admission and throughout their hospital course. 17 In the cancer patient hypoactive delirium due to hypoxia, infection, or metabolic encephalopathy is often missed and misinterpreted as fatigue, depression, or sedation from opioid pain medication.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer predominately affects individuals age 65 and older, and older age and a pre-existing psychiatric condition are associated with a missed diagnosis of delirium which is often misinterpreted as dementia in this population. 16,18,19 …”
Section: Introductionmentioning
confidence: 99%